Jamčevalni zahtevki pri pogodbah o dobavi digitalnih vsebin ali digitalnih storitev - Korošec, Masha (Pravni letopis, 2021)
The article analyses the remedies set out in Directive 2019/770 to which the consumer may resort if the contract for the supply of digital content and digital services is not performed correctly. The Directive was adopted in May 2019 and is a part of the Commission`s Digital Single Market Strategy that aims to ensure a high level of consumer protection and harmonisation of main rights and obligations of the parties to a sales contract. The main issue faced by the European legislature concerned the adequacy of remedies available to the consumer in the event of a breach of such contracts. Remedies honed to respond to the sale of tangible items do not necessarily translate well into the digital market, since the main subject matter of the contract is not a physical item but intangible data such as video files, e-books, music files, etc. The Directive addresses the consumer`s rights both in case of a failure to supply and in case of a lack of conformity and is based on the current EU consumer acquis. However, it brings quite a few novelties to the European legal area, among others it distinguishes between objective and subjective requirements for conformity and introduces the responsibility for the integration of digital content, furthermore, given that the digital content and services are constantly developing, it also addresses the issue of providing the updates to consumers.
Keywords: digitalizacija; digitalna tehnika; obligacijska razmerja; pogodbeno pravo; potrošništvo; tehnološke inovacije; varstvo potrošnikov